Active Control of a Chaotic Fractional Order Economic System - Baskonus, Haci Mehmet; Mekkaoui, Toufik; Hammouch, Zakia; Bulut, Hasan (Mdpi, 2015)
In this paper, a fractional order economic system is studied. An active control technique is applied to control chaos in this system. The stabilization of equilibria is obtained by both theoretical analysis and the simulation result. The numerical simulations, via the improved Adams-Bashforth algorithm, show the effectiveness of the proposed controller.